Specific antibacterial activity of copper alloy touch surfaces in five long-term care facilities for older adults. Issue 3 (March 2020) - Colin, M.; Charpentier, E.; Klingelschmitt, F.; Bontemps, C.; De Champs, C.; Reffuveille, F.; Gangloff, S.C.
Summary: Background: Pathogens involved in healthcare-associated infections can quickly spread in the environment, particularly to frequently touched surfaces, which can be reservoirs for pathogens. Aim: The purpose of this study was to investigate naturally occurring bacterial contamination on touch surfaces in five French long-term care facilities and to compare bacterial populations recovered from copper and control surfaces. Methods: More than 1300 surfaces were sampled. The collected bacteria were identified to obtain a global view of the cultivable bacterial populations colonizing touch surfaces. Haemolytic colonies and putative pathogens were also screened using specific agar plates and then identified with matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry. In total, more than 3400 colonies were analysed. Findings: Staphylococcus and Micrococcus were the two predominant genera present on touch surfaces, respectively occurring on 51.8% and 48.0% of control surfaces. In these facilities with relatively low bioburden, copper surfaces efficiently reduced the occurrence frequencies of three genera: Staphylococcus, Streptococcus and Roseomonas. Pathogenic species such as Staphylococcus aureus, Enterococcus faecalis and E. faecium were observed in very few samples. In addition, meticillin-resistant S. aureus was observed on five control surfaces and one copper surface. Conclusion: Contamination of healthcare facilities touch surfaces can be the source for the spread of bacteria through the institution. This in situ study shows that the frequency of the contamination as well as the specific bacterial population bioburden is reduced on copper alloy surfaces.